MASALAH KERUSAKAN DAN KEHILANGAN BAGASI TERCATAT PENUMPANG PESAWAT UDARA DI BANDARA INTERNASIONAL SEPINGGAN - BALIKPAPAN - Fitriyani Fitriyani (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACTWith conditions changing strategic environment, and current flight organizer needs, many of which are new policy set within the provisions of the transport number 1 in 2009. Act No. 1 of 2009 governing the flight in Indonesia, in Article (1) number 1 states 'flight is a unified system consisting of the use of airspace, aircraft, and airports, air transport, air navigation, safety and security, the environment and supporting facilities and other facilities. While this paper has theoretical and practical benefits, this paper is expected to be used as the initial information in the field of law for the academic community to know more about the development of air transport law, especially regarding the transport of goods. This paper is practically can provide input for a personal author, community government, and the parties that are directly related to the activity of an air transport, so as to provide air transport services are good and comfortable for passengers.